2019
DOI: 10.1371/journal.ppat.1007958
|View full text |Cite
|
Sign up to set email alerts
|

The mutation of Transportin 3 gene that causes limb girdle muscular dystrophy 1F induces protection against HIV-1 infection

Abstract: The causative mutation responsible for limb girdle muscular dystrophy 1F (LGMD1F) is one heterozygous single nucleotide deletion in the stop codon of the nuclear import factor Transportin 3 gene (TNPO3 ). This mutation causes a carboxy-terminal extension of 15 amino acids, producing a protein of unknown function (TNPO3_mut) that is co-expressed with wild-type TNPO3 (TNPO3_wt). TNPO3 has been involved in the nuclear transport of serine/arginine-rich proteins such as splicing factors and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 68 publications
1
27
0
1
Order By: Relevance
“…ADAM10 and TPNO3 have been suggested as targets of this miRNA, and their part in nuclear transport of the preintegration complex is of the essence for the establishment of proviral DNA [84]. Rodriguez-Mora et al showed that a defective mutation in TPNO3 confers protection against HIV infection [85]. This fact bolsters the relevance of this miRNA in the control of the virus and further research is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM10 and TPNO3 have been suggested as targets of this miRNA, and their part in nuclear transport of the preintegration complex is of the essence for the establishment of proviral DNA [84]. Rodriguez-Mora et al showed that a defective mutation in TPNO3 confers protection against HIV infection [85]. This fact bolsters the relevance of this miRNA in the control of the virus and further research is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The main causes of control of HIV viremia reported to date include allelic variants in genes encoding HIV coreceptors, such as CCR5, 14,15 CCR2, 31 and CXCR6; 32 the cell surface density of CXCR4 33 and CCR5 coreceptors; 34 mutation of the transportin 3 gene; 19 the level of expression of the CXCR4 ligand SDF‐1 35 and the CCR5 ligands RANTES and MIP‐1α; 36 HLA class I genotypes such as HLA‐B * 27, 37 HLA‐B * 57, 38 and HLA‐B * 39; 39 production of cytokines such as IL‐10; 40 cellular immune responses including anti‐p24 Gag CD4 + T cells 41 and anti‐p24 gag and anti‐Pol CD8 + T cells; 42,43 and humoral immune responses, such as anti‐gp41 env 44 and anti‐gp120 env neutralizing antibodies 45 . Restriction against HIV infection can also apply at the level of host cells (so‐called intrinsic antiviral immunity) via expression of antiviral factors including APOBEC3G, 46 TRIM5‐alpha, 47 TRIM22, 48 TRIM11, 49 tetherin/CD317, 50 SAMHD1, 51 or SERINC5; 52 RNA silencing through microRNAs such as miRNA‐1236 and miRNA‐29; 53,54 proviral long terminal repeat (LTR) silencing by methylation; 55 histone deacetylases HDAC; 56 or by histone H1‐mediated Tat repression, 57 among others (for a more comprehensive list, see Turner and Margolis 58 ).…”
Section: Types Of Hiv Patientsmentioning
confidence: 99%
“…In other words, researchers should segregate the major players in HIV restriction that lead to elite control in HESN individuals from factors that have a secondary role, even if the latter have been shown in vitro to delay or completely inhibit HIV replication. The newly described genetic HIV resistance associated with the nuclear import factor transportin 3 gene ( TNPO3 ) 19 may hopefully join this category of major factors.…”
Section: Beside Ccr5‐delta32 There Is Space For Other Hiv‐restrictiomentioning
confidence: 99%
See 1 more Smart Citation
“…La dystrophie musculaire des ceintures autosomique dominante de type D2 (ou LGMD 1F d'après l'ancienne nomenclature) est causée par une mutation hétérozygote (délétion d'un nucléotide dans le codon de terminaison de la traduction) dans le gène TNPO3 codant le facteur d'import nucléaire Transportine 3 [1]. Cette mutation entraîne un allongement de la protéine de 15 acides aminés au niveau carboxy-terminal, ce qui produit la co-expression de la protéine sauvage (TNPO3_wt) et de celle mutée (TNPO3_ mut) dont la fonction est inconnue.…”
Section: Résuméunclassified